On 17-4PH stainless steel dental implant for premolar 4 in canine under compressive loading: effect of solid and octet metastructure - Bharat Kalia; Rupinder Singh; Bahadur Singh Pabla; Gurwinder Singh (Exploration of BioMat-X)
Aim: The study aims to analyze the canine’s implant behaviour under compressive loading [to be installed in a maxilla at a premolar 4 (PM4) location]. After simulation of various mechanical properties, the 17-4 precipitate hardened (PH) stainless steel (SS) prototypes were successfully 3D printed by powder bed fusion (PBF) process with solid and octet metastructure to reduce stress shielding. Methods: The maxillary PM4 tooth of a male German shepherd dog was selected as the subject for the proposed study. As PM4 loading in canines is analogous to compressive loading conditions, finite element analysis (FEA) under compression was performed to compare simulated results of solid and octet meta-structure specimens. Solid and octet meta structure-based compression samples were prepared per ASTM E9 standard using SolidWorks software. The octet metastructure was designed with node and connector diameters of 0.5 mm each on 3DXpert software. Further FEA analysis of designed compression samples was performed using Ansys Workbench by selecting 17-4PH SS material at loading conditions of 800 N and 5,000 N. Results: The FEA results at the loading of 800 N show that maximum Von-Mises stress in the case of the solid and octet meta structure-based compression specimen was 10.029 MPa and 131.61 MPa, respectively. Further, the maximum Von-Mises strain for the solid and octet meta-structure-based specimens was 0.000049163 and 0.00067179, respectively. Similarly, deformation (in mm) for solid and octet truss lattice-based compression samples were 0.00075097 and 0.001451, respectively. The results observed at the loading condition of 5,000 N followed a pattern similar to that of 800 N loading conditions. Conclusions: Octet metastructure-based compression sample showed encouraging potential for withstanding maximum compression loading applicable to canine (800 N) while lowering the impacts of stress shielding. The safety factor against failure (N) was 4.33 and 62.31 for the octet meta-structure and solid compression samples, respectively.